THE EFFECT OF INTEGRATIVE LEARNING MODEL TYPE THREADED IN READING AT CLASS VIIIIII STUDENTS OF SMP IT FAJAR ILAHI 1 BATAM - Susanty, Ratna (Publikasi dan UKI Press UKI Toraja., 2022)
The aim of this research is to identify the effectiveness of the threaded type integrative learning model in learning to read for Class VIII students at SMP IT Fajar Ilahi 1 Batam. The researcher was applied pre-experimental design the population is the seven grade students of SMP IT Fajar Ilahi 1 Batam in academic year 2021/2022. Based on data analysis, hypothesis testing, and the results of the discussion that has been presented, the researcher can conclude that the results of the research that has been carried out are that the application of the Threaded Type Integrative Learning Model in Reading Learning for Class VIII Students at SMP IT Fajar Ilahi 1 Batam can improve students' reading abilities